How the new European data protection regulation affects clinical research and recommendations? - Demotes-Mainard, Jacques; Cornu, Catherine; Guérin, Aurélie (Therapie, 2019)
Clinical research on human subjects or their data is confronted with conflicting requirements with, on one hand, the principle of open science (transparency and data sharing), the possibilities offered by big data and the reuse of healthcare or research data, and on the other, changes to the regulatory and legislative framework, including the general data protection regulation (GDPR). A roundtable was organized in Giens, France in October 2018 to identify problem areas, the need for clarification and streamlining, and to make recommendations to promote clinical research while ensuring a high level of patient protection. After details were given about these developments, the roundtable participants were able to propose recommendations, primarily (1) to clarify: what is considered anonymized data, and what is "public interest" within the meaning of the GDPR; (2) for the French data protection authority (CNIL) to continue preparing reference methodologies to simplify the approval system; (3) to promote the secondary use of data by making it easier to inform patients and obtain broad patient consent, by specifying the circumstances under which their withdrawal and opposition rights apply, so as to limit the risk of bias; (4) to facilitate access to data warehouses by providing technological and methodological aids. The roundtable also recommends increasing discussions between authorities in Europe on research topics, encouraging French authorities to contribute to the preparation of codes of conduct and setting up a voluntary harmonization procedure to coordinate the opinions of data protection authorities, while ensuring that key documents are available in English.